A Study of the Problems of Economic Translation in Abstracts of Translated Research for Al-Eqtisadi Magazine Issued by the University of Basrah - Hadi Salim, Lect. Alyaa (Basra studies journal, 2023)
Language is a way to share information and connect with those around us, but machines need to understand the intricacies of language and how we, as humans, communicate to take advantage of it. This paper deals with the theoretical and practical analysis of "economic translation". As a process, economic translation is a multi-step, complex act of intercultural bilingual communication aimed at creating the closest "natural equivalent" of the target text. It is also characterized by high equivalence with the original text. Economic translation as a text is difficult to process in the same way as the original text, which is not the same due to cultural and language differences. This study reveals that the interdisciplinary nature of economic translation makes it difficult to define its status. According to the analysis, the term "economic translation" has a broader meaning. This is due to the fact that it works in different areas of activity (business, economy, trade, etc.). This element influences source texts of different genres and styles. The practical part of this paper is devoted to the most common problems faced by translators of economic documents. The researchers used translated abstracts of articles published in AL Eqitisadi Newsletter issued by the University of Basrah as a sample to investigate Economic translation problems and their solutions.